Turning a new pager: a Silicon Valley firm is mixing the latest Net technologies with the old-fashioned pager. - Holland, Lorien (Far Eastern Economic Review, 2000)
The Silicon Valley company GWcom is developing a product that combines the pager with the latest Internet technologies. Victor Wang, president of GWcom, contends that these new pagers are pioneers of wireless Internet access. China has the potential to become a huge market for this form of technology. GWcom's frequency is separate from the crowded mobile-phone frequencies because it has the first and only technology to be licensed by Beijing to operate in the radio-frequency spectrum allocated for mobile-data transmission. Plus, GWcom can afford to spend on expansion. However, GWcom's success will depend on targeting, value, and quality, according to Bill Wang, co-founder of the Beijing-based China Research Corp.